Regulatory B cells drive immune evasion in the tumor microenvironment and are involved peritoneal metastasis in gastric cancer - Yuta Fujiwara; Jun Kinoshita; Mari Shimada; Hiroto Saito; Toshikatsu Tsuji; Daisuke Yamamoto; Hideki Moriyama; Motoki Horii; Sachiyo Nomura; Takashi Matsushita; Yasuhiko Yamamoto; Noriyuki Inaki (Scientific Reports)
Abstract Peritoneal metastasis (PM) of gastric cancer (GC) has an immune escape environment. Regulatory B cells (Bregs), characterized by IL-10 production, play an important role in the tumor immunity; however, the function of Bregs in PM remains unclear. We investigated the frequency and effects of Bregs on other immune cells in the PM using clinical specimens and mouse models of PM. In the peripheral blood and ascites, Breg frequency was significantly higher in patients with GC with PM than in those without PM. In clinical PM samples, Breg frequency was an independent prognostic factor. In the mouse PM model, peritoneal tumors showed higher Breg infiltration than subcutaneous tumors. In the PTEN-deficient PM model, activation of Bregs promoted ascites and peritoneal tumor growth, decreased the infiltration of CD8+ T cells, and increased the infiltration of M2 macrophages. In contrast, treatment with wortmannin, a phosphatidylinositol 3-kinase (PI3K) inhibitor, suppressed Breg infiltration, resulting in decreased M2 macrophage infiltration and increased CD8+ T cell infiltration. Bregs are indicated to be involved in immunosuppression of PM and are promising targets for improving the efficacy of immunotherapy against PM.